2013
DOI: 10.1007/s12298-013-0174-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment around the fruit set region on growth and yield of watermelon [Citrullus lanatus (Thunb.) Matsum. and Nakai]

Abstract: The present experiment was aimed to study the effect of imposing modulated temperature treatments 14°C and 18°C, around the fruiting region of watermelon plants, and to estimate the economic feasibility of the temperature treatments based on energy consumption for heating. Watermelon cultivar 'Sambok-gul' was selected and sown on perlite beds in a plastic house under controlled conditions at Watermelon Farm, Jeongeup-Jeonbuk, longitude 35°31′ 47.51N, 126°48′48.84E, altitude 37 m during the early spring season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Watermelon (Citrullus lanatus L.), a member of the Cucurbitaceae family, is one of the top five mostconsumed fresh fruits globally. In many areas of the world, chilling stress owing to early-spring low temperature is a major environmental stress threatening the watermelon industry 1,2 . Among the several techniques that are commonly used to cope with chilling stress, grafting is one of the most-effective and cost-saving approaches [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Watermelon (Citrullus lanatus L.), a member of the Cucurbitaceae family, is one of the top five mostconsumed fresh fruits globally. In many areas of the world, chilling stress owing to early-spring low temperature is a major environmental stress threatening the watermelon industry 1,2 . Among the several techniques that are commonly used to cope with chilling stress, grafting is one of the most-effective and cost-saving approaches [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Its yield is significantly influenced by these abiotic stresses such as drought, salinity and cold [52]. Many studies showed that auxin is involved in stress response, and a quantity of auxin transporter genes are associated with abiotic stress responses.…”
Section: Resultsmentioning
confidence: 99%
“…Watermelon is an important cucurbit crop and its output value accounted for more than 10% of the total output value of the vegetable industry in China. Watermelon seedling’s growth stops below 10 °C and cannot survive below the 1 °C [52]. Salinity and drought are the major environmental stresses in plant agriculture worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Originating from Africa and tropical regions in Asia, watermelon is sensitive to low temperatures. The best growing conditions for watermelon are between 21 and 29 • C. When the temperature drops to 10 • C, watermelon stops growing and it even dies at temperatures below 1 • C [1]. Extreme weather frequently occurs in China, especially during the seedling stage, such as winter, late autumn, and early spring, in which watermelon usually suffers cold stress.…”
Section: Introductionmentioning
confidence: 99%